Análisis tecno-tipológico de la cerámica arqueológica depositada en el museo de Chalán, provincia de Chimborazo - Quinte Guaiña, Genesis Valeria (2025)
The objective of the research was to conduct a techno-typological analysis of the ceramics in the Chalán Museum to characterise their form, manufacturing techniques, and cultural relevance, and to contribute to the knowledge and conservation of Andean archaeological heritage. A qualitative and interpretive approach was applied based on the techno- typological method adapted by De Barros (2024). Thirty-nine pieces were observed, and data were processed using analysis sheets, photographic records, field journals, and spreadsheets. The study showed that 100% of the pieces were made using the cord- marked technique. The Puruhá phase predominated (90%), followed by the Colonial phase (5%) and 2% without an identified cultural phase. The most common forms were pots, bowls, and jugs, mainly used for domestic and ceremonial purposes related to death. The results confirm the persistence of ancestral traditions in the Puruhá region and highlight the importance of the Chalán Museum as a repository of material memory. Finally, the relevance of valuing local archaeological heritage to strengthen conservation and dissemination strategies in academic and community contexts is emphasised.